Factores familiares que influyen en la deserción escolar de los adolescentes pertenecientes al programa justicia juvenil restaurativa del ministerio publico distrito fiscal la libertad en el año 2014. - Gil Carlos, Rithzy Noelia (2015)
In recent years the high dropout rate in Peru has grown so excessive, although this problem is studied in different areas of society, these studies focus on vulnerable populations living in poverty or extreme poverty. No clutch this research relates dropout family factors that accommodate this problem, which likewise is related to unlawful conduct to law brings many other problems that limit the quality of life of adolescents. It can be said that the dropout is not an individual decision, often is influenced by contextual factors that are identified during the research process and analyzed in adolescents with unlawful behavior belonging to the Public Prosecutor of La Libertad Restorative Justice Program. The study of this problem is organized into three chapters, the first part of enhanced study discloses the reality in which the problem studied unfolds, as well as the history of research previously conducted and analyzed from the same profession, are discloses equally theories that explain the problem to study; under the statement of the problem, hypotheses are expressed, and the objectives for which research, just as the methods and techniques are based. As a second part of the research is divided into four chapters, which are organized as follows. In CHAPTER I General characteristics of the study population are shown, such as gender, age, grade completed before dropout and dropout age. In Chapter II takes into account family factors that influence the decision to dropout, a study of family communication, family functioning, relationships are made, as well as some points related to the degree of culturalism of parents or heads home. CHAPTER III shows the results obtained from the economic factors influencing dropout population investigated, analyzed here, family economic support, TESIS individual current economic situation and family, housing conditions and economic activity performed by adolescents deserters. Finally in Chapter IV, social factors and networking opportunities, both labor and institutional influencing dropout teenagers prosecutors Restorative Justice Program are analyzed. Therefore such research and analysis points studied come from factors that contribute to dropout, it is concluded that low socioeconomic status and the existence of certain problems in families are in a poor school performance and parental involvement scarce. Are presented and made some recommendations to both the development of prevention programs and for the development of future research on the subject and the user population.